SINTESIS FAUJASITE DARI ABU LAYANG BATUBARA : Pengaruh Refluks dan Penggerusan Abu Layang Batubara terhadap Kristalinitas Faujasite - Sutarno Sutarno; Yateman Arryanto; Arief Budhyantoro (Jurnal Matematika & Sains, 2004)
Synthesis of Faujasite from coal fly ash has been conducted which involved reflux, grinding fusion and hydrothermal reaction. Coal fly ash is refluxed with hydrochloric acid 5 M at 90 oC for 5 hours. Grinding effect of refluxed coal fly ash on Faujasite synthesis has been studied as other variable on synthesis of Faujasite. Coal fly ash is mixed with NaOH pellet which NaOH : coal fly ash ratio = 1.2, and then fused at 550 oC for 1 hour. Fused coal fly ash is mixed with 100 ml distilled water, stirred and aged for 24 hours. The resulted solution was then reaeted with hydrothermal bomb autoclave at 100 oC for 3 days. The result was characterized with X-ray diffraction using diffractometer shimadzu 3001. The experimental data showed that coal fly ash refluxed with hydrochloric acid 5 M increased in Si/Al ratio of coal fly ash. Synthesis of Faujasite with coal fly ash refluxed with HCl 5 M as raw material produced good crystallinity Faujasite, but the used of unrefluxed coal fly ash as raw material on synthesis of zeolite gave hydroxysodalitet. Synthesis of Faujasite from ungrand coal fly ash whichh is refluxed with HCl 5 M gave better Faujasite crystallinity than that of the grund one.